Multihop Data Transmission Using LoRa Technology - Manalu, Istas Pratomo; Sigiro, Marojahan Timbul Mula; Simatupang, Frengki; Manik, Andreas A. P.; Sitohang, Necia G. A.; Pardede, Goldi (Program Studi Teknik Mesin Universitas Pamulang, 2025)
The use of Long Range (LoRa) technology in Internet of Things (IoT) networks has grown rapidly to support applications that require wide coverage with low energy consumption. However, physical obstacles and indoor use often cause significant signal attenuation, reducing range and increasing energy consumption. To overcome these limitations, this study implements multihop communication using LoRa repeaters to extend network coverage. In this study, DHT11 sensors are used to measure air temperature and humidity, with data transmitted through a multihop scheme consisting of three LoRa devices: transmitter, repeater, and receiver. The purpose of this study is to analyze the performance of LoRa communication in a multihop scheme, focusing on measuring key parameters such as Received Signal Strength Indicator (RSSI), Signal-to-Noise Ratio (SNR), and Packet Loss. Point-to-point experiments showed that the RSSI was in the range of -103 dBm to -105.5 dBm, while in multihop, the recorded RSSI ranged from -102 dBm to -105 dBm. Meanwhile, the SNR in point-to-point ranged from -2 dB to -22 dB, and in multihop, the SNR value varied from -1.00 dB to -14.50 dB. At a distance of 1.5 kilometers, the point-to-point method suffers from a high packet loss of 65%, with only 23 out of 67 packets received, indicating inadequate performance. In contrast, the multihop method successfully reduces the packet loss to only 0.8%, with 33 out of 36 packets received, indicating improved data transmission quality and reliability. Tests show that the use of LoRa repeaters in multihop networks can significantly extend communication range and improve energy efficiency, with successful data delivery and performance that meets expectations. This research makes an important contribution to understanding the implementation of multihop LoRa networks, especially in the context of IoT applications that require wide coverage in congested environments.